EFEKTIVITAS PERAN KOMISI INFORMASI PROVINSI RIAU DALAM MENYELESAIKAN SENGKETA INFORMASI PUBLIK - Edriani, Yori; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Information Commission of Riau Province is an independen institution formed by the law No.14 of 2008 on public disclosure, Riau Govenor regulation No. 72 of 2012 on information commission province formation. But Information Commission of Riau Province is not maximized in realizing the public disclosure particulary with regard to buged and finace of public institution information because of blocked imitations member, buged and operationa finance. The problem in this study is how the effectiveness role of Information Commission of Riau Province on finished pubic information dispute and factors effecting effectiveness role of Information Commission of Riau Province on finished public information dispute. Purpose from this study is to know effectiveness role Information Commission of Riau Province on finished public information dispute an factors effecting effectiveness role information commission riau province on finished pubic informastion dispute.The concept of the theory is that organization, information disclosure, and organization effectiveness. This study use qualitative resarch methods to study descriptive data. The collecting data, the resarcher used interview,observation and documentation.The result of this study indicate that the effectiveness role Information Commission of Riau Province on finished public information dispute has not been effective, visible from stage of effectiveness are not fulfilled. The factors that effecting effectiveness role Information Commission of Riau Province on finished public information dispute is ability to adapt, productivity, job satisfaction, resource utilization, the ability to produce. Kata kunci : Effectiveness, Public Information Dispute, Information Commission Province